1993
DOI: 10.1063/1.858666
|View full text |Cite
|
Sign up to set email alerts
|

Origin of turbulence-producing eddies in a channel flow

Abstract: A principal theoretical problem in understanding wall turbulence is the determination of how turbulence is created and sustained, i.e., the explanation of how energy is transferred from the mean flow to the turbulence. Flow-oriented vortical eddies have been associated with large Reynolds stresses and with the production of turbulence in the viscous region close to the wall. Their creation and evolution are investigated in a high-resolution direct numerical simulation of turbulent flow in a channel. An importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
110
1
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 189 publications
(131 citation statements)
references
References 13 publications
18
110
1
2
Order By: Relevance
“…Note that in linear evolution, the −(∂w/∂x)(∂u/∂y) term corresponds to the Ω∂u s /∂x generation term, responsible for creation of a ω x sheet (and x-circulation generation) in the streak trough region (figure 13b; see § 4.2). In the nonlinear regime of STG, the −(∂w/∂x)(∂u/∂y) term is largest in magnitude over all other terms, consistent with fully developed turbulence (Brooke & Hanratty 1993). However, this term actually contributes to the thin tail (C in figure 27c) of the near-wall ω x layer, not to the main vortex (SP).…”
Section: Evolutionary Vortex Dynamicsmentioning
confidence: 93%
See 2 more Smart Citations
“…Note that in linear evolution, the −(∂w/∂x)(∂u/∂y) term corresponds to the Ω∂u s /∂x generation term, responsible for creation of a ω x sheet (and x-circulation generation) in the streak trough region (figure 13b; see § 4.2). In the nonlinear regime of STG, the −(∂w/∂x)(∂u/∂y) term is largest in magnitude over all other terms, consistent with fully developed turbulence (Brooke & Hanratty 1993). However, this term actually contributes to the thin tail (C in figure 27c) of the near-wall ω x layer, not to the main vortex (SP).…”
Section: Evolutionary Vortex Dynamicsmentioning
confidence: 93%
“…Prior studies (e.g. Sendstad & Moin 1992;Brooke & Hanratty 1993) have proposed that near-wall ω x sheets (like those generated by STG) 'roll-up' due to their self-advection, an effect represented by the ω x advection terms in (18). In purely two-dimensional flow, near-wall vorticity sheets can roll up via two distinct mechanisms, illustrated in figure 28: (i) on the left side of a +ω x layer above a free-slip wall, with dipole-like 'head-tail' formation due to the wall image vorticity (see Jimenez & Orlandi 1993), as illustrated in the sequence in figure 28(a), or (ii) on the right side of a +ω x layer attached to a no-slip wall, due to lifting of the wall-generated ω x by a parent vortex, as in vortex wall-rebound (see Orlandi 1990), as shown by the sequence in figure 28(b).…”
Section: Evolutionary Vortex Dynamicsmentioning
confidence: 99%
See 1 more Smart Citation
“…35 These results are in agreement with previous findings in plane Couette and Poiseuille flows. Jimenez and Moin 40 and Brooke and Hanratty 41 found that the largest contribution to the generation of streamwise vorticity comes from the tilting term ͑−‫ץ‬u / ‫ץ‬y͒͑‫ץ‬w / ‫ץ‬x͒. The latter authors computed the contribution of the term ͑‫ץ‬u / ‫ץ‬z͒͑‫ץ‬v / ‫ץ‬x͒ to be less than 10% of total production.…”
Section: -11mentioning
confidence: 99%
“…This special VVCS structure at y s,0 is called the limiting VVCS structure, whose characteristics are believed to be important for turbulence modelling. Brooke & Hanratty (1993) in their DNS study of channel flow presented the evidence for quasi-streamwise vortices for y + < 40, while Christensen & Adrian (2001) suggested that hairpin packets cannot reach more than 100 wall units. We have not be thorough at the current moderate Re, but a qualitative feature is discernible.…”
Section: Vvcs In a Turbulent Channel Flowmentioning
confidence: 99%